Multivessel vs. culprit vessel-only percutaneous coronary intervention in ST-segment elevation myocardial infarction with and without cardiogenic shock - Wu, Jing; Wang, Yonggang; Li, Chenguang; Ji, Honglei; Zhao, Wenyi; Tong, Qian; Zhang, Mingyou (Frontiers in Cardiovascular Medicine, 2022)
Objectives: This study investigated the impact of multivessel percutaneous coronary intervention (PCI) vs culprit-only PCI in ST-segment elevation myocardial infarction (STEMI) with and without cardiogenic shock in the United States using data from the National Inpatient Sample. Background: Early revascularization of the culprit vessel is the most effective treatment for reducing the risk of mortality from acute STEMI with and without cardiogenic shock. However, the trend and impact of multivessel PCI during the index hospitalization on in-hospital outcomes are unknown. Methods: The National Inpatient Sample was queried from October 2015 to 2019 for hospitalizations with STEMI. The impact of multivessel PCI on in-hospital outcomes of patients with and without cardiogenic shock was evaluated. Results: Of 624,605 STEMI hospitalizations treated with PCI, 12.5% were complicated by cardiogenic shock. Among hospitalizations without cardiogenic shock, 15.7% were treated by multivessel PCI, which declined from 20.8% in 2015 to 13.9% in 2019 (Ptrend<0.001). Multivessel and culprit-only PCI had similar rates of In-hospital mortality (2.4% vs 2.3%, p=0.027) and major adverse cardiac and cerebrovascular events (MACCE; 7.4% vs 7.2%, p=0.072). Among hospitalizations with cardiogenic shock, 22.1% were treated by multivessel PCI, which declined from 29.2% in 2015 to 19.4% in 2019 (Ptrend<0.001). Multivessel PCI was associated with higher rates of in-hospital mortality (30.9% vs 28.4%, p<0.001) and MACCE (39.9% vs 36.5%, p<0.001) than culprit-only PCI. Conclusions: The frequency of multivessel PCI for STEMI with and without cardiogenic shock is declining. Multivessel PCI is associated with worse in-hospital outcomes for STEMI with cardiogenic shock but not for STEMI without cardiogenic shock.